Protective Effect of Ocimum Gratissimum Against Lead Induced Histological Changes in Rabbit Liver - Fatima Qaiser, Shakeela Nazir, Ashiq Hussain, Asma Kazi, Aisha Aziz, Maheen Rana, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Since it is well-established that lead exposure can have negative effects on hematological, biochemical, and hepatic parameters, a significant number of research efforts have been focused on antioxidants that are capable of treating as well as preventing these alterations. Objective: The purpose of this study was to explore the influence of Ocimum Gratissimum (OG) extract on the hemato-biochemical parameters of the livers of adult Wistar rats and the lead-induced toxicity of the livers. Method: For the aim of this investigation, a total of 70 adult Wistar rats were separated into seven groups, with each group containing 10 rats. Group A acted as the control group, Group B received 120 mg/kg of lead, and Group C received 375 mg/kg of OG. Group A was the only group that received no treatment. The role of the control group was played by Group A. Before administering the OG dosages of 375 and 750 mg/kg to Group D and Group E, respectively, a lead dose of 120 mg/kg was administered to both groups. In Group F, participants received 375 mg/kg of OG extract followed by 120 mg/kg of lead, whereas in Group G, participants received 120 mg/kg of lead followed by 1,190 mg/kg of ascorbic acid. After the conclusion of each oral treatment, which lasted a total of 21 days, the animals were slaughtered and their blood and liver tissues were collected for subsequent histological and biochemical testing. The results of these tests will be shown in the following paragraphs. Results: The research led to the discovery that the Control group had a rise in their average body weight, but the B group experienced a fall in their weight. The findings of the biochemical tests revealed that when compared to the Control group and the other treatment groups, the levels of liver enzymes such as ALT, AST, GGT, and ALP in Group B were considerably higher than in the other treatment groups (p 0.05). The results of the histological analysis of the liver tissues revealed degenerative alterations, such as localized necrosis and aggregated inflammatory cells in Group B. These findings were found in the liver tissues of the group B patients. In contrast, the liver tissue in Groups D, E, F, and G that had been treated with the extract exhibited ameliorative alterations. These results may be seen in the table below